Consumer Preferences and Sugar Marketing Strategy By Stated-Owned Enterprise Plantations in North Sumatra - Sari, Fadhila Cynthia; Zulbainarni, Nimmi; Harianto (School of Business, Bogor Agricultural University (SB-IPB), 2023)
Sugar is a commodity that recreates a valuable role in the daily consumption of Indonesian. This study aims to determine the attributes and combinations that influence consumer preferences in buying branded white crystal sugar and the marketing strategies that can be applied in marketing Walini sugar at PT. Perkebunan Nusantara II. Analysis of consumer preferences in this study using the conjoint analysis method. Meanwhile, the marketing strategy analysis uses the A'WOT method. Based on the conjoint analysis results, it was concluded that the most important attribute in evaluating consumers' interest in branded white crystal sugar is color. Subsequently, the best combinations of attributes that consumers favored were obtained, namely white color, selling points in minimarkets, sales promotions in the form of discounts/coupons/gifts, vibrant and attractive packaging, slight sugar texture, and sugarcane's aroma. Furthermore, based on the results of the A'WOT analysis, seven alternative marketing strategies were obtained. The priority strategy with the highest weighted value is expanding the cooperation network with potential distributor agents. Keywords: A’WOT, conjoint analysis, consumer preference, marketing strategy, white crystal sugar